2020
DOI: 10.3920/jiff2018.0037
|View full text |Cite
|
Sign up to set email alerts
|

Edible insect marketing in Western countries: wisely weighing the foodstuff, the foodie, and the foodscape

Abstract: Despite secular consumption of insects in many regions of the world, this practice remains marginal in Western countries. Although entomophagy is slowly gaining mainstream visibility, it often triggers consumer acceptance only on a trial basis driven in part by adventurousness, environmental concerns, health benefits, food security issues, or a combination thereof. This paper draws from the consumer and ingestive behaviour literatures and from the growing entomophagy sphere of knowledge in order to surface pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…The second aim was to observe the interplay between baby schema cuteness and marketing claims. Marketing claims have been the focal point of most previous studies on edible insect packaging elements (Berger et al, 2018;House, 2016;Legendre and Baker, 2021;Marquis et al, 2020). Hence, it is essential to develop a more holistic understanding of the combined effect of cuteness on this central component of packaging design.…”
Section: Research Aims and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second aim was to observe the interplay between baby schema cuteness and marketing claims. Marketing claims have been the focal point of most previous studies on edible insect packaging elements (Berger et al, 2018;House, 2016;Legendre and Baker, 2021;Marquis et al, 2020). Hence, it is essential to develop a more holistic understanding of the combined effect of cuteness on this central component of packaging design.…”
Section: Research Aims and Objectivesmentioning
confidence: 99%
“…Marketing claims have been the focal point of most previous studies on edible insect packaging elements (Berger et al. , 2018; House, 2016; Legendre and Baker, 2021; Marquis et al. , 2020).…”
Section: Research Aims and Objectivesmentioning
confidence: 99%
“…For Westerners to perceive insects as an actual foodstuff, strategies aiming to overcome reluctance should be directed towards modifying individual and social mental representations. Besides marketing strategies that can contribute to alleviating such consumer‐level barriers (Marquis et al, 2020), exposure and familiarisation have been identified as avenues that can help further overcoming reluctance towards edible insects (Tan et al, 2015). Pedagogical edible insect farming activities in schools hold the potential for creating enjoyable learning environments to address food and nutrition issues, while providing knowledge about how to farm and cook with insects.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of insect protein as a rich source of nutrients to modern food chains may eliminate the protein gap. At the same time, edible insects may be revived as an alternative food source and a component of food products, in particular in Western civilizations [ 14 , 15 , 16 ]. Entomophagy is a new component of the food production system in the European Union.…”
Section: Introductionmentioning
confidence: 99%